(untitled) (Pain medicine, 2021)
We aimed to study the influence of prolonged administration of fentanyl on postoperative pain, intraabdominal pressure and mechanical lungs’ changes that may happen in neonates in early postoperative period. 30 newborns (in the period from January 2017 to May 2021) with gastroschisis were divided into two groups accordingly to the method of analgesia (14 – morphine hydrochloride; 16 – prolonged infusion of fentanyl). Lungs’ mechanical characteristics, effectiveness of postoperative analgesia, abdominal wall relaxation was studied by monitoring of dynamic compliance (Cdyn), pressure and flowvolume loops, capnography. Apprising analgesia status, we measured hemodynamic, SаO2, blood level of cortizol, Creactive protein (CRP), glucose, analyzed postoperative pain syndrome using visual analogue scales (VAS). Intraabdominal pressure (IAP) was controlled by Cron. For statistic analysis we used Student’s ttest. In the group with morphine, thete was the increase of IAP by 11–12 cm H2O, being stable during some period of time, and also variable levels of pain according to VAS, the increasing of CRP from 0.8 ± 0.25 mg/dl by 5 mg/dl, cortisol by 674.4 nmol/l, and blood glucosae rate – 7.4 mmol/l. Periods with high traumatic effects and poor analgesia (morphine group) reasoned the increasing IAP, step by step dynamic compliance decreasing in 3.4 times, resistance increasing in 2.42 times and PIP rising till 22 cm H2O. Direct correlation between IAP increase and lungs’ mechanical changes took place. The study has demonstrated that prolonged administration of fentanyl prevented high increase of IAP, CRP, levels of glucose and cortizol and changes of VAS data, lungs’ mechanical characteristics.